Savant Abilities in Autism Spectrum Disorder: A Systematic Literature Review and Meta-Analysis - Chang, Trisha Chereen; Mahardani, Putu Nandika Tungga Yudanti; Wati, Dyah Kanya (Jurnal Kedokteran Meditek, 2026)
Introduction: Autism Spectrum Disorder (ASD) is a neurodevelopmental condition marked by social-communication difficulties and restricted, repetitive behaviors. Despite these challenges, some individuals with ASD demonstrate exceptional abilities in one or more area, which is known as Savant. Until now, factors linked to savant abilities are still poorly understood. This research compared cognitive, social, and behavioral functioning between savant and non-savant individuals diagnosed with ASD. Methods: A comprehensive search was conducted to identify studies comparing cognitive, social, or behavioral characteristics between the two groups. Thirteen studies met the inclusion criteria and were included in the quantitative synthesis. Statistical analyses were performed using R software. Results: Savant individuals with ASD showed significantly higher cognitive functioning than non-savant peers (SMD = 0.73, 95% CI: 0.59–0.87). Social functioning differences were negligible and non-significant (SMD = −0.03, 95% CI: −0.22–0.16). Behavioral traits, including repetitive behaviors, were slightly more pronounced among savants but were not statistically significant (SMD = 0.17, 95% CI: −0.07–0.40). Conclusions: Savants with ASD exhibit higher cognitive functioning but do not show significant differences in social or behavioral functioning compared to their non-savant peers, highlighting that enhanced abilities are not necessarily accompanied by corresponding deficits.